AIRWAYS-ICPs (European Innovation Partnership on Active and Healthy Ageing) from concept to implementation. Issue 4 (April 2016) - Bousquet, Jean; Barbara, Cristina; Bateman, Eric; Bel, Elisabeth; Bewick, Mike; Chavannes, Niels H.; Cruz, Alvaro A.; Haahtela, Tari; Hellings, Peter W.; Khaltaev, Nikolai; Lodrup Carlsen, Karin; Muraro, Antonella; et al.
Chronic respiratory diseases (CRDs) are major non-communicable diseases (NCDs) [1, 2] that induce a significant burden. Asthma often occurs along the life cycle from early childhood, affecting 30 million children and adults under 45 years of age in Europe [3]. Chronic obstructive pulmonary disease (COPD) has an estimated annual death rate of over 3 million people globally [1, 2]. The annual direct and indirect costs in the 28 European Union (EU) countries due to COPD or asthma are estimated at 48 billion euros and 34 billion euros respectively [3]. Rhinitis occurs in over 100 million people in Europe, and indirect costs are enormous [4]. Asthma is a common risk factor for COPD [5, 6]. CRDs impact ageing and should be prevented, recognised and managed across the life cycle to promote active and healthy ageing (AHA). There is an urgent need to act globally. AIRWAYS-ICPs is a European Union initiative on multi-sectoral care pathways for chronic respiratory diseases http://ow.ly/Yndtw